The effect of temperature on mate preferences and female-female interactions in Syngnathus abaster - Silva, K. (2013)
Despite much effort to ascertain the consequences of temperature variation for a wide range of animal performance traits, the effect of temperature on interactions among organisms is still poorly understood. The present work tests for a direct influence of water temperature on sexual recognition, mate preferences and femaleefemale interactions in the pipefish, Syngnathus abaster. Three experiments were conducted by monitoring time spent in the vicinity of conspecifics at three water temperatures intended to reflect sea water temperatures before the onset of reproduction (15 ºC) and during the early (18º C) and late breeding season (24 ºC). Four major results emerged: (1) S. abaster can visually discriminate potential mates from fish of the same sex; (2) males and females responded differently with the former diverting their attention towards the opposite sex at intermediate (18º C) and high temperatures (24º C), while the latter only showed a significant interest in potential mates at 24 ºC, devoting an equal amount of interest towards both males and females at 18º C; (3) at breeding season water temperatures, both sexes discriminated against smaller partners, preferring larger ones; (4) different-sized females adopted distinct temperature-modulated behavioural responses, possibly because large dominant females, which engage in competition at 18º C, constrained the reproduction of smaller ones, which seem to compete only at 24º C. These results highlight the importance of temperature as an effective agent in the modulation of S. abaster reproductive behaviour. Considerations on the ecological significance of the observed behavioural patterns are also discussed.